1993
DOI: 10.1111/j.1365-2389.1993.tb02325.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate leaching from grazed grassland lysimeters: effects of fertilizer input, field drainage, age of sward and patterns of weather

Abstract: Drained and undrained grassland lysimeter plots were established in 1982 on a clay loam of the Hallsworth series at a long-term experimental site in south-west England. The plots were continuously grazed by beef cattle, and received fertilizer at either 200 or 400 kg N ha -I per annum to the existing permanent sward, or at 400 kg N ha-' to a new sward, reseeded to perennial ryegrass following cultivation. Drainage water was monitored at V-notch weirs and sampled daily for the analysis of nitrate-N. Seven years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
148
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(162 citation statements)
references
References 28 publications
13
148
1
Order By: Relevance
“…The key principle is to maximize the uptake of nutrients by the pasture plants. Factors such as the amount of manure applied (Scholefield et al, 1993) and the intensity of grazing (Ryden et al, 1984) are known to influence nitrogen leaching and were included in a model developed by Hansen et al (2000) to compare organic v. conventional farming. However, due to lack of data, such models are not yet at a stage of development though to be able to deal with all the processes involved.…”
Section: Gill Smith and Wilkinsonmentioning
confidence: 99%
“…The key principle is to maximize the uptake of nutrients by the pasture plants. Factors such as the amount of manure applied (Scholefield et al, 1993) and the intensity of grazing (Ryden et al, 1984) are known to influence nitrogen leaching and were included in a model developed by Hansen et al (2000) to compare organic v. conventional farming. However, due to lack of data, such models are not yet at a stage of development though to be able to deal with all the processes involved.…”
Section: Gill Smith and Wilkinsonmentioning
confidence: 99%
“…In intensively grazed dairy pasture systems, although the amount of NO3--N leached is affected by inputs of N fertilisers and organic waste effluents (Scholefield et al 1993;Di et al 1998aDi et al ,b, 1999Ledgard et al 1999a;Silva et al 1999;Monaghan et al 2000), the largest contribution comes from the N returned from the animal urine (Ball et al 1979;Ryden et al 1984;Field et al 1985;Silva et al 1999;Di & Cameron 2000, 2002b. In a grazed pasture, between 60-90% of the N ingested by the grazing animal is returned to the pasture in the urine and dung and more than 70% of the N returned is in the urine (Haynes & Williams 1993;Jarvis et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that in a grazed pasture system, direct leaching losses of NO 3 -from applied fertiliser nitrogen (N) or farm dairy effluent (FDE) are relatively small compared with the leaching losses from animal urine patches (Scholefield et al 1993;Di et al 1998Di et al , 1999Di et al , 2002Silva et al 1999;Ledgard et al 1999;Di & Cameron 2002b;Monaghan et al 2002).…”
Section: Introductionmentioning
confidence: 99%